What drives the consistent use of long-lasting insecticidal nets over time? A multi-method qualitative study in mid-western Uganda. (December 2016) - Strachan, Clare; Nuwa, Anthony; Muhangi, Denis; Okui, Albert; Helinski, Michelle; Tibenderana, James
Abstract Background The distribution of long-lasting insecticidal nets (LLINs) through universal coverage campaigns is a widely adopted approach for the prevention of malaria at scale. While post-distribution surveys play a valuable role in determining cross-sectional levels of LLIN retention and use, as well as frequently cited reasons for non-use, few studies have explored the consistency of LLIN use over time, within the expected lifespan of the net, and the factors which may drive this. Methods In this qualitative study, 74 in-depth interviews were conducted with (male) household heads and (female) caregivers of children in LLIN recipient households, as well as community health workers, in Buliisa, Hoima and Kiboga districts in Uganda, 25–29 months following a LLIN mass campaign distribution. A triangulation approach to data analysis was taken, incorporating thematic analysis, most significant change and positive deviance. Results The factors found to be most influential in encouraging long-term LLIN use were positive experience of net use prior to the distribution, and appreciation or awareness of a range of benefits arising from their use, including protection from malaria as well as importantly, other health, lifestyle, social and economic benefits. Social support from within the community was also identified as an important factor in determining continued use of LLINs. Net use appeared to be more consistent amongst settled urban and rural communities, compared with fishing, pastoralist, refugee and immigrant communities. Conclusions A multitude of interplaying factors encouraged consistent LLIN use in this setting. Whilst the protection of malaria remains a powerful motivator, social and behaviour change (SBC) strategies should also capitalize on the non-malaria benefits of net use that provide a long-term rationale for consistent use. Where supplies are available, SBC campaigns should promote replacement options, emphasizing ongoing net care and replacement as a household responsibility, thus reducing dependence on free distributions. The triangulation approach to qualitative data analysis enabled increased confidence in the validity of findings and an enhanced contextual understanding of the factors promoting consistent net use in mid-western Uganda. The approach should be considered when designing future studies to explore factors driving net retention and use trends.